From hovels to homes : the provision of public housing in Irish provinicial towns, 1890 - 1945 - Connell, Peter (Trinity College (Dublin, Ireland). Department of History, 2017)
In the mid-1940s a quarter of all private dwellings in Irish provincial towns had been built by their local councils in the preceding fifty years. In comparative terms this represented a high level of state involvement in housing in a country lacking a substantial industrial working class or an influential social democratic politics, two key factors in promoting state housing in other countries. Two basic research questions are explored. Why were levels of public housing so high in Irish towns? And what factors lay behind the wide variations in public housing provisions across those towns?
Embargo End Date: 2022-04-30
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin, 2017